Central Nervous System Effects of Malus domestica (Apple) Extracts: Behavioural, Biochemical, and Neuropharmacological Findings in Swiss Albino Mice. - Kumar, Umesh; K, Saravanan (Journal of Neonatal Surgery, 2025)
Malus domestica (apple) is rich in polyphenols with potent antioxidant and neuroprotective properties. This study evaluated the central nervous system (CNS) effects of ethanolic and petroleum‑ether apple extracts (50 and 100 mg/kg, p.o.) administered daily for 14 days in Swiss albino mice. Behavioral assays assessed locomotor activity, anxiety‑like and depression‑like behaviors, and memory performance. Biochemical analyses measured oxidative‑stress markers (MDA, SOD, GSH, CAT), key neurotransmitters (dopamine, serotonin, acetylcholine), and pro‑inflammatory cytokines (TNF‑α, IL‑6, NF‑κB). Extract‑treated mice exhibited significant anxiolytic and antidepressant‑like effects alongside improved memory. These behavioral benefits were accompanied by reduced brain MDA levels, enhanced antioxidant enzyme activities, suppressed neuroinflammation, elevated central dopamine and serotonin, preserved acetylcholine, and inhibition of monoamine oxidase‑A. Collectively, these findings demonstrate that M. domestica extracts bolster CNS function via antioxidant, anti‑inflammatory, and monoaminergic/cholinergic modulation, highlighting their therapeutic potential for neuropsychiatric and neurodegenerative disorders